Developing and Validating the English Teachers’ Cognitions About Grammar Teaching Questionnaire (TCAGTQ) to Uncover Teacher Thinking - Zhang, Lawrence Jun; Sun, Qiang (Frontiers in Psychology, 2022)
It is well acknowledged that teachers play a significant role in enhancing student learning and that investigating teachers’ cognitions about teaching is a first and important step. Although much research into teachers’ cognitions about grammar teaching has been conducted in various socio-cultural contexts, little has been reported on cognitions of Chinese teachers of English as a foreign language (EFL) so far. Such understanding is of primary importance to student success in language learning given the sociocultural context where grammar takes a lion’s share in high-stakes examinations. In order to address this research gap, we developed and validated the Chinese EFL Teachers’ Cognitions about Grammar Teaching Questionnaire (TCAGTQ). Two subsamples (n1=314, n2=215) were randomly invited to respond to the TCAGTQ and the data were then subjected to exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to test the validity and reliability of the instrument. The EFA excluded eight items from the TCAGTQ and generated six factors with 27 items. The CFA result from the other subsample supported a six-factor model with a good model fit. Moderate correlations between the six factors also supported the predictive validity of the questionnaire, showing that the TCAGTQ is a valid and reliable inventory for measuring Chinese university EFL teachers’ cognitions about grammar teaching. Our findings suggest that the TCAGTQ can be used as a useful tool for teachers to self-assess their professional practice for improving teaching.